Versatility in self-assembly and morphology of non-coded anthranilic acid and phenylglycine based dipeptide stereoisomers. Issue 20 (6th May 2022) - Dolai, Gobinda; Giri, Rajat Subhra; Mandal, Bhubaneswar
Abstract : Molecular self-assembly and morphology of non-coded anthranilic acid and l /d -phenylglycine containing dipeptides have been investigated. Interestingly, significant morphological changes were observed just by reversing the peptide sequence. Abstract : Beauty in the self-assembly patterns of isomeric dipeptides of Boc-Ant-l -Phg-OMe (1 ) bearing two rigid, unnatural amino acids (Ant: anthranilic acid, Phg: phenylglycine) is demonstrated. Additionally, self-assembly and morphological variation by the incorporation of a d -amino acid, Boc-Ant-d -Phg-OMe (2 ), and corresponding reversed sequences of both peptides, Boc-l -Phg-Ant-OMe (3 ) and Boc-d -Phg-Ant-OMe (4 ), respectively, are explored. FT-IR study indicated the presence of conformational heterogeneity in the reverse peptides. SC-XRD suggested that 1 and 2 contain helical and β sheet-like layer architectures, respectively, whereas 3 and 4 exhibited different kinds of helical structures, sheet-like layer architectures, and molecular channels. Optical microscopy, FESEM, FETEM, and AFM images suggested that both C-terminal l - and d -Phg containing peptides (1 and 2 ) self-assembled to form a vesicular morphology and their reversed sequences, i.e., N-terminal l - and d -Phg containing peptides (3 and 4 ), displayed a well-organized rod-like fiber structure. TGA analysis revealed that the obtained supramolecular structures have significant thermal stability.